(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Advertising is explained as mass communication ofinformation intended to persuade buyers to buy products and with a view tomaximizing a company’s profits. Communication achieves the purpose of gettingone’s ideas across to the other party. But, more important purpose ofcommunication is to draw the desired response from the target audience.